"Chasing hope": Parents' perspectives on complementary and alternative interventions for children with autism in Kazakhstan. (October 2020) - An, Sofiya; Kanderzhanova, Akbota; Akhmetova, Assel; Foster, Faye; Chan, Chee Kai
In post-Soviet Kazakhstan, the system of care for children with autism has been transforming over the past three decades. There is little known about the use of complementary and alternative medicine by families raising autistic children in the post-Soviet region. An exploratory qualitative focus group design was employed to study parents' experiences of using complementary and alternative medicine focusing on the perceived factors driving the utilization of complementary and alternative medicine by families of autistic children and the availability of complementary and alternative medicine. Six focus groups were conducted in five cities of diverse geographical locations in Kazakhstan. Data were analyzed using a framework analysis. Two overarching themes and subthemes are developed. The first "unmet needs" relates to predisposing factors that motivate parents to complementary and alternative medicine uptake and the second "chasing hope" relates to enabling factors that facilitate parents' uptake of complementary and alternative medicines. In summary, parents of autism spectrum disorder children in Kazakhstan face multiple challenges when seeking treatment for their children's condition and implement whatever complementary and alternative medicine interventions available. A decision to use, and the choice of intervention, mainly comes from perceptions of having no other choice rather than from rational decisions based on efficacy of complementary and alternative medicines. This study provides the first empirical conceptualization of parents' motives for choosing complementary and alternative medicine in Kazakhstan. Lay abstract: The article reports the findings of a qualitative research study on how and why parents of autistic children in Kazakhstan utilize complementary and alternative medicine. We found that parents turn to complementary and alternative medicine because of the lack of professional care options available to them and in pursuit for hope and opportunities for their children with ASD.